Monitoring of physiological heterogeneity of microbial populations in environmental biotechnological processes - Saeid Rezaeinejad (2012)
Most of the approaches to the studies of microbial populations in environmental engineering systems have presumed that a microbial population comprises cells with the same physiological properties. However, it is known that individual cells within a microbial population have different physiological states. The purpose of this study was to investigate physiological heterogeneity in the eukaryotic population of Saccharomyces cerevisiae and prokaryotic population of Escherichia coli, and also within microbial community (e.g., microbial granules) found in environmental engineering systems. The first objective was to identify different subpopulations of S. cerevisiae and E. coli populations using flow cytometry analysis of membrane integrity, membrane potential and respiratory activity. The second objective was to examine sensitivity of different subpopulations of bacterial cells to chlorine disinfectant. The third objective was to analyse spatial distribution of viable and dead cells within bacterial granule of Pseudomonas veronii. Fluorescent probes such as propidium iodide (PI), DiBAC4(3) and CTC in combination with flow cytometry and confocal laser scanning microscope were used for the assessment of physiological states of microbial cells at single-cell level. This study revealed that for the assessment of cell viability of eukaryote S. cerevisiae, the most practical method was the determination of membrane integrity using PI. Two subpopulations with high and low activities of alcohol dehydrogenase were detected in the growing population of S. cerevisiae. The share of respiratory active cells of E. coli population under long-term starvation dropped to 5%, whereas approximately 50% of cells maintained the membrane potential. The results of cell viability determination by PI in combination with flow cytometry indicated that CT values required for 2-log inactivation (CT99) for E. coli cell populations with µ=0.9 h-1 and µ=0.2 h-1 were 0.06 and 0.09 mg min l-1, respectively. A thin stratum of dead cells (<20 µm) was observed in the outside edge of granule produced from cells of P. veronii, after simultaneous staining with PI and DiBAC4(3).